Hipocracy in the Performance of State Civil Apparatus and Public Services in Mojokerto District/City: New Public Services (NPS) Perspective - Ammaya Sabilah; Tri Sulistyaningsih (PERSPEKTIF, 2023)
The bureaucratic problem that pervades becomes a pathology that weakens existence as well as fosters a negative stigma against ingrained government bureaucracy where bureaucracy is considered a disease (bureaupathology). In addition, the current bureaucracy tends to be patrimonialistic, which is no longer effective and efficient (over consuming and under producing). Every country or even an agency in local government in Indonesia is still very difficult to avoid various kinds of problems in the administration of the bureaucracy, especially related to acts of corruption. Therefore this research was conducted to explain the impact of hypocracy on the performance of apparatus and public services in Mojokerto Regency/City. This research was studied using qualitative methods through literature study through various sources such as journals, official websites, laws, and books related to related topics and subjects. The results of this study are that bureaucratic diseases such as corruption greatly affect the performance of the apparatus in providing services to the public. So, the low quality of the bureaucracy due to bureaucratic pathology (hipocracy) can reduce the effectiveness and efficiency of the apparatus in providing services to the public, therefore the New Public Service perspective is very important to be implemented and used as a guide for bureaucratic reform or reform.